Measuring national power in the postindustrial age : analyst's handbook - Tellis, Ashley J. (MR (Series) ;, 2000)
This handbook is designed to complement the main report (RAND/MR-1110-A). It is intended to provide the analyst the substance of the concepts and metrics for assessing national power without presenting extensive background or the analytic underpinning contained in the main document.